ANALISIS DAMPAK KEGIATAN EKSTRAKURIKULER TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR - Mutsaqofah, Marsa Bila; Afifah, Aulya Nur; Amalia, Tiana; Amelia, Decenni (JIPIS, 2025)
This study aims to analyze the impact of extracurricular activities on student learning outcomes in elementary schools. The research method used is descriptive qualitative research with data collection techniques carried out online through google form using a questionnaire. Respondents or informants in this study were elementary school teachers in the Bekasi City or Regency area. The results showed that extracurricular activities have a significant positive impact on student development, both academically and non-academically. Students involved in these activities showed increased self-confidence, independence and social skills, as well as being more critical, disciplined, creative and motivated to learn. The supportive environment in extracurricular activities contributes to the development of students' positive attitudes and behaviors, helping them learn to work together, become responsible leaders, and care for the environment. These activities also encourage students to actively participate, with motivational support from teachers who help them recognize their interests and talents and provide appreciation for achievements. In addition, it is important to evaluate the effectiveness of extracurricular activities through feedback from students and participation in social activities to ensure that the goal of developing students' social and physical skills is achieved.